Humor in the classroom a guide for language teachers and educational researchers - Bell, Nancy 1969-; Pomerantz, Anne (New York, NY Routledge, 2016)
Humor in the Classroom provides practical, research-based answers to questions that educational researchers and language teachers might have about the social and cognitive benefits that humor and language play afford in classroom discourse and additional language learning. The book considers the ways in which humor, language play, and creativity can construct new possibilities for classroom identity, critique prevailing norms, and reconfigure particular relations of power.
Language, Communication, and Education -- Humor and Language Play -- Understanding Classroom Talk -- Playing it Safe -- Humor, Learning, and Additional Language Development -- Teachers and Humor: Weighing the Risks and Benefits -- Teaching with Humor -- Teaching about Humor -- Researching Humor and Language Play.
Includes bibliographical references and index.
Keywords: Language and languages -- Study and teaching; Language and languages -- Humor; Wit and humor in education; Teaching -- Humor